Simultaneous Ablation of the Catalytic AMPK α-Subunit SNF1 and Mitochondrial Matrix Protease CLPP Results in Pronounced Lifespan Extension - Heinz, Daniela; Krotova, Evgeniia; Hamann, Andrea; Osiewacz, Heinz D. (Frontiers in Cell and Developmental Biology, 2021)
Organismic aging is known to be controlled by genetic and environmental traits. Pathways involved in the control of cellular metabolism play a crucial role. Previously, we identified a role of PaCLPP, a mitochondrial matrix protease, in the control of the mitochondrial energy metabolism, aging and lifespan of the fungal aging model Podospora anserina. Most surprisingly, we made the counter-intuitive observation that the ablation of this component of the mitochondrial quality control network leads to lifespan extension. In the current study we investigated the role of energy metabolism of P. anserina. An age-dependent metabolome analysis of the wild-type and a PaClpP deletion strain verified differences and changes of various metabolites in cultures of the PaClpP mutant and the wild type. Based on these data we generated and analyzed a PaSnf1 deletion mutant and a deltaPaSnf1/deltaPaClpP double mutant. In both mutants PaSNF1, the catalytic alpha-subunit of AMP-activated protein kinase (AMPK) is ablated. PaSNF1 was found to be required for the development of fruiting bodies and ascospores, the progeny of sexual reproduction of this ascomycete, and impacts mitochondrial dynamics and autophagy. Most interestingly, while the single PaSnf1 deletion mutant is characterized by a slight lifespan increase, simultaneous deletion of PaSnf1 and PaClpP leads to a pronounced lifespan extension. This synergistic effect is strongly reinforced in the presence of the mating-type “minus”-linked allele of the rmp1 gene. Compared to the wild type, culture temperature of 35 °C instead of the standard laboratory temperature of 27 °C leads to a short-lived phenotype of the deltaPaSnf1/deltaPaClpP double mutant. Overall our study provides novel evidence for complex interactions of different molecular pathways involved in mitochondrial quality control, gene expression, and energy metabolism in the control of organismic aging.